2010
DOI: 10.1530/eje-10-0464
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin and vascular endothelial growth factor as risk markers for severe hypoglycaemia in type 1 diabetes

Abstract: Objective: Circulating erythropoietin (EPO) and vascular endothelial growth factor (VEGF) increase during hypoglycaemia and may represent protective hormonal counter-regulatory responses. We tested the hypothesis that low levels of EPO and VEGF are associated with a higher frequency of severe hypoglycaemia in a cohort of patients with type 1 diabetes. Design: Prospective observational follow-up study. Methods: Totally 219 patients with type 1 diabetes (41% females, age 46G13 years (meanGS.D.), duration of diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…However, the distribution of data were collected from a wide range of applications reveals asymmetry. Examples arise, for instance, in wind speed data (Zhu and Genton 2012), temperature data (North et al 2011), soil and air pollution data (Jafari Khaledi and Rivaz 2009;Zareifard and Jafari Khaledi 2013), precipitation data (Xu and Genton 2017) and diabetes data (Kristensen et al 2010). The skew-normal (SN) distribution, introduced by Azzalini (1985), has been used successfully to model data sets that have asymmetric behavior.…”
Section: Introductionmentioning
confidence: 99%
“…However, the distribution of data were collected from a wide range of applications reveals asymmetry. Examples arise, for instance, in wind speed data (Zhu and Genton 2012), temperature data (North et al 2011), soil and air pollution data (Jafari Khaledi and Rivaz 2009;Zareifard and Jafari Khaledi 2013), precipitation data (Xu and Genton 2017) and diabetes data (Kristensen et al 2010). The skew-normal (SN) distribution, introduced by Azzalini (1985), has been used successfully to model data sets that have asymmetric behavior.…”
Section: Introductionmentioning
confidence: 99%
“…However, the distribution of data were collected from a wide range of applications reveals asymmetry. Examples arise, for instance, in wind speed data (Zhu and Genton, 2012), temperature data (North et al, 2011), soil and air pollution data (Jafari Khaledi and Rivaz, 2009; Zareifard and Jafari , precipitation data (Xu and Genton, 2017) and diabetes data (Kristensen et al, 2010). The skew-normal (SN) distribution, introduced by Azzalini (1985), has been used successfully to model data sets that have asymmetric behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The evidences has shown that not only stressors with a hypoxic component but also other stressors in the brain, such as neurotoxicity and hypoglycemia, are able to induce changes in the expression level of EPO (Morishita et al, 1997; Brines and Cerami, 2008; Kristensen et al, 2010; Yamada et al, 2011; Kastner et al, 2012; Nguyen et al, 2014; Rainville et al, 2016; Nekoui and Blaise, 2017). Although EPO gene expression in the brain is also induced by activation of hypoxia-inducible factors, EPO is not the primary inducer of EPOR (Chin et al, 2000; Grasso et al, 2004); therefore, the regulatory mechanisms of both the production and the processing of EPOR transcripts are uncertain, even under hypoxic conditions.…”
Section: Introductionmentioning
confidence: 99%